Storytelling-Based Audiovisual Media Learning in Improving the Skills of Grade IV Elementary School Students - Utami, Gusti Ayu Putri; Kristiantari, Maria Goreti Rini; Pramunditya, Didith (International Journal of Language and Literature, 2024)
Students' listening skills at the elementary school level are often less than optimal, especially with the use of conventional methods that tend to be monotonous and uninteresting. This often happens in Indonesian language learning, which requires more attention from students. This study aims to explore the effectiveness of the storytelling learning model based on audiovisual media in improving the listening skills of fourth-grade elementary school students and to compare it with conventional methods. This study used a quasi-experimental design with a Non-equivalent pretest-posttest control group design. The research sample consisted of 45 students divided into two groups: an experimental class taught with a storytelling model based on audiovisual media and a control class using conventional methods. Data were collected through multiple-choice objective tests and analyzed using descriptive statistics and t-tests. The results showed a significant difference in listening skills between the experimental and control groups. This study concludes that the storytelling learning model based on audiovisual media is efficacious in improving students' listening skills. The implication of this study is the importance of implementing innovative learning strategies that pay attention to the cognitive and psychological aspects of students to improve the effectiveness of Indonesian language learning in elementary schools.